Epidemiologic study of orthodontic retention procedures - Padmos, Jens A D; Fudalej, Piotr S; Renkema, Anne Marie (American journal of orthodontics and dentofacial orthopedics, 2018)
INTRODUCTION: The aims of this study were to survey current retention procedures applied by Dutch orthodontists and to examine their acquaintance with "unintentionally active retainers." METHODS: A questionnaire was sent to all 306 Dutch orthodontists involved in patient treatment. Questions were clustered in 4 parts: (1) general information, (2) retention procedures, (3) characteristics of wire materials for bonded retainers, and (4) acquaintance with "unintentionally active retainers." RESULTS: The response rate was 98%. The most applied retention modality in the maxillary arch was a combination of a removable and a bonded retainer (54%); in the mandibular arch, mainly a bonded retainer without a removable retainer was used (83%). Bonded retention was aimed to be lifelong for the maxillary arch (90%) and the mandibular arch (92%). Mean removable retention duration was 2 years. Vacuum-formed retainers were used more frequently and Hawley-type retainers less frequently. The wire materials used for bonded retainers were diverse. All orthodontists were familiar with unintentionally active retainers; 44% believed this phenomenon is caused by the properties of round multistrand wires. The opinion that unwanted changes in tooth position can arise due to the properties of round multistrand wire material was associated with changing the wire material (P <0.005). CONCLUSIONS: Lifelong retention with bonded retainers continues to increase. All orthodontists were acquainted with unintentionally active retainers and their impact. There is a need to identify all causative factors of inadvertent tooth movement in relation to bonded retainers and to prevent the onset of unintentionally active retainers.
Keywords: vazba zubní; mandibula; průzkumy a dotazníky; Orthodontic Anchorage Procedures; Practice Patterns, Dentists'; Dental Bonding; Surveys and Questionnaires; Orthodontic Wires; Orthodontists; lidé; ortodontické přístroje - design; Mandible; malokluze; Orthodontic Retainers; Orthodontics, Corrective; Malocclusion; postupy ortodontického kotvení; maxila; Epidemiologic Studies; ortodoncie korekční; ortodontisté; ortodontické dráty; Maxilla; ortodontické retainery; epidemiologické studie; Orthodontic Appliance Design; vzorové postupy ve stomatologii; Humans